Zmienność stanów wody rzeki Czerna Wielka w latach 1961-2010 - Choiński, Adam; Ptak, Mariusz; Łabędzka-Gardy, Maria (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2014)
Daily observations of the levels of water in the Czerna Wielka river have been followed by an analysis of the relevant fluctuations. It has been established that in the Żagań profile (closing the catchment), the course of the water levels show a downward trend. The average water level in the timeframe 1961-2010 amounted to 108.3 cm (42.63 inches). The highest annual level occurred in 1981 (136.8 cm = 53.85 inches) while the lowest level was recorded in 1991 (82.1 cm = 32.32 inches). As for specific seasons, the water levels tend to be clearly highest in the winter months (with peaks in January and March) while the lowest levels are characteristic of the vegetation season (July–August). What is more, an analysis has been carried out of the water levels in two other observation stations located in an upper part of the catchment, where a reverse trend has been recorded (in 1971-1993). This indicates that in the specified time, the water level has tended to rise, unlike in the Żagań station in the same period of analysis. This situation may result from the catchment’s diversity with respect to the natural conditions (lithology) as well as human activity (hydraulic structures).
Keywords: Czerna Wielka river; water levels; Bory Dolnośląskie